2006
DOI: 10.1086/506328
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Markers and Behavioral Correlates of Sexually Transmitted Infections in a Nonclinical Sample of Adolescent and Young Adult Women

Abstract: The high prevalence of STIs in this nonclinical sample of young women suggests the need for ongoing screening and prevention interventions that target young, healthy, sexually active women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
39
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
4
39
1
Order By: Relevance
“…This finding may indicate that the sex partners of non-Hispanic black women also had a higher prevalence of T. vaginalis infection than did the sex partners of women in other racial/ethnic groups [27]. Although studies for selected clinic populations have also found that the prevalence of trichomoniasis among non-Hispanic black women was higher than that among women from other racial/ethnic groups [28][29][30], this study is the first, to our knowledge, to describe this finding in a nationally representative sample of reproductive-aged women.…”
Section: Discussionmentioning
confidence: 98%
“…This finding may indicate that the sex partners of non-Hispanic black women also had a higher prevalence of T. vaginalis infection than did the sex partners of women in other racial/ethnic groups [27]. Although studies for selected clinic populations have also found that the prevalence of trichomoniasis among non-Hispanic black women was higher than that among women from other racial/ethnic groups [28][29][30], this study is the first, to our knowledge, to describe this finding in a nationally representative sample of reproductive-aged women.…”
Section: Discussionmentioning
confidence: 98%
“…Insight into the mechanisms that drive the burden of these infections is essential for disease control. In addition to age, HIV infection, and behavioral factors, microbiological characteristics, including bacterial load, may play an important role in the risk of transmission, clinical presentation, and course of infection (6,(11)(12)(13)(14). Chlamydial load has been associated with clinical presentation, severity of infection, and transmissibility in animal models and in patients with ocular C. trachomatis infection (15-17).…”
mentioning
confidence: 99%
“…Sexual health is an important arena in which to study men's health seeking behaviors as their decisions about whether or not to seek care in this area affects not only their own health, but that of their sex partners as well. The asymptomatic nature of many STIs; Boyer et al, 2006;Todd, Haase, & Stoner, 2001) means that during adoles cence and young adulthood, the peak years for such infections, sexually active young men are in need of STI screening even when they feel fine, a particularly hard-to-motivate form of health care seeking behavior. Finally, the elemental position that men's sexual behavior assumes in their masculinity constructions and their perceived need for SHC increases the potential impact of these constructions on their health care seeking behavior in this arena.…”
mentioning
confidence: 99%